N-C-Compactness - Nasir, Ahmed Ibrahem; Esmaeel, Rana Bahjat (Al-Nahrain Journal of Science, 2018)
In this paper, we defi ne another types of Compactness on bitopological spaces, namely “N-C-Compactness”, “S-C-Compactness” and “pair-wise C- ompactness”, and we review some remarks, propositions and examples are also reviewed about these types. Also, we discussed the relationships among them.